Image forming material for toner binder
A toner binder composition with a polyester resin and silicone resin addresses durability and releasability issues, achieving a wide fixing width for high-speed commercial and industrial printing.
Patent Information
- Application Number
- JP2024103303
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-06
- Filing Date
- 2024-06-26
- Publication Date
- 2025-01-20
AI Technical Summary
Existing toner materials lack sufficient durability, mold releasability, and a wide fixing width, making them unsuitable for high-speed commercial and industrial printing applications.
A toner binder composition containing a polyester resin and a silicone resin, where the polyester resin is derived from ethylene glycol and terephthalic acid, and the silicone resin is a cured product, with a specific weight ratio of 0.1 to 1% in the image forming material.
The composition provides improved durability, releasability, and a wide fixing width, enhancing the performance of toners in high-speed printing applications.
Smart Images

Figure 2025009990000001 
Figure 2025009990000002 
Figure 2025009990000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an imaging material for a toner binder. [Background technology]
[0002] In recent years, with the development of electrophotographic systems, efforts are being made to expand the application of electrophotographic technology to commercial printing, industrial printing, and other applications. In the field of commercial printing and industrial printing, stable high-speed printing is required, so a certain level of low-temperature fixability and hot offset resistance, that is, a wide fixing width, is required. In addition, it is necessary to meet requirements such as durability against shear and compression caused by agitation that the toner receives inside the cartridge so as to prevent the generation of fine powder. The image forming material has a large effect on the toner characteristics as described above. Known examples of the image forming material include polystyrene resin, styrene-acrylic resin, polyester resin, epoxy resin, polyurethane resin, and polyamide resin. Polyester resin is particularly attracting attention because it is easy to achieve a balance between low-temperature fixing ability and hot offset resistance. For example, a toner that has excellent low-temperature fixing properties and offset resistance by incorporating a release agent into the toner has been disclosed (Patent Document 1). However, it cannot be said that they have sufficient durability, releasability, and wide fixing width for use as toners in commercial printing and industrial printing, and improvements in these respects are desired. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 7-244398 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide an image-forming material for a toner binder which is excellent in durability and releasability and is used for a toner having a wide fixing width. [Means for solving the problem]
[0005] The present inventors have made extensive investigations and have arrived at the present invention. That is, the present invention is an image-forming material for toner binders, which contains a polyester resin (A) obtained by polycondensing an alcohol component and a carboxylic acid component, and a silicone resin (C), in which the alcohol component of the polyester resin (A) contains ethylene glycol, the carboxylic acid component contains terephthalic acid, the silicone resin (C) is a cured product of a curable silicone resin, and the weight ratio of the silicone resin (C) in the image-forming material is 0.1 to 1% by weight. Effect of the Invention
[0006] According to the present invention, it is possible to provide an image forming material for a toner binder which is excellent in durability and releasability and is used for a toner having a wide fixing width. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The image-forming material for toner binder of the present invention comprises a polyester resin (A) obtained by polycondensation of an alcohol component and a carboxylic acid component, and a silicone resin (C), wherein the alcohol component of the polyester resin (A) contains ethylene glycol, the carboxylic acid component contains terephthalic acid, the silicone resin (C) is a cured product of a curable silicone resin, and the weight ratio of the silicone resin (C) in the image-forming material is 0.1 to 1 wt %. The image forming material for toner binder of the present invention will be described below in detail.
[0008] The image-forming material for a toner binder of the present invention contains a polyester resin (A) obtained by polycondensing an alcohol component and a carboxylic acid component. The polyester resin (A) is a polyester resin in which the alcohol component contains ethylene glycol and the carboxylic acid component contains terephthalic acid.
[0009] When the carboxylic acid component contains terephthalic acid, the durability of the toner can be improved, and the chargeability can be improved.
[0010] The alcohol component constituting the polyester resin (A) may contain a polyol component (x) in addition to ethylene glycol. The polyol component (x) includes a diol (x1) other than ethylene glycol and a trihydric or higher polyol (x2). These may be used alone or in combination of two or more.
[0011] Examples of the diol (x1) include alkylene glycols having 3 to 36 carbon atoms (propylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol), alkylene ether glycols having 4 to 36 carbon atoms (diethylene glycol, triethylene glycol, dipropylene glycol, Examples of the alkylene diol include alkylene glycols, alkylene glycols, aryl alkylene diols, aryl alkylene diols, and the like), alicyclic diols having 6 to 36 carbon atoms (1,4-cyclohexanedimethanol, hydrogenated bisphenol A, and the like), (poly)alkylene oxide adducts of the above-mentioned alicyclic diols (preferably having an average number of moles added of 1 to 30), aromatic diols [monocyclic dihydric phenols (e.g., hydroquinone, etc.) and bisphenols, etc.] and alkylene oxide adducts of the above-mentioned aromatic diols (preferably having an average number of moles added of 2 to 30).
[0012] The alkylene oxide adducts of the bisphenols are obtained by adding alkylene oxide (hereinafter, "alkylene oxide" may be abbreviated as AO) to the bisphenols.
[0013] The bisphenols include those represented by the following general formula (1). HO-Ar-P-Ar-OH (1) [In the formula, P represents an alkylene group having 1 to 3 carbon atoms, -SO2-, -O-, -S- or a direct bond, and Ar represents a phenylene group in which a hydrogen atom may be substituted with a halogen atom or an alkyl group having 1 to 30 carbon atoms.]
[0014] Specific examples of bisphenols include bisphenol A, bisphenol F, bisphenol B, bisphenol AD, bisphenol S, trichlorobisphenol A, tetrachlorobisphenol A, dibromobisphenol F, 2-methylbisphenol A, 2,6-dimethylbisphenol A, and 2,2'-diethylbisphenol F, and two or more of these can be used in combination.
[0015] Examples of the alkylene oxide to be added to the bisphenol include alkylene oxides having 2 to 30 carbon atoms, such as ethylene oxide (hereinafter, "ethylene oxide" may be abbreviated as EO), propylene oxide (hereinafter, "propylene oxide" may be abbreviated as PO), butylene oxide, tetrahydrofuran, and combinations of two or more of these.
[0016] Among these diols (x1), from the viewpoints of low-temperature fixability and heat-resistant storage stability, alkylene glycols having 3 to 36 carbon atoms and alkylene oxide adducts of aromatic diols are preferred, alkylene glycols having 3 to 10 carbon atoms and alkylene oxide adducts of bisphenols (average number of moles added is preferably 2 to 5), alkylene glycols having 3 to 6 carbon atoms and alkylene oxide adducts of bisphenol A (average number of moles added is preferably 2 to 5) are more preferred, and EO and / or PO adducts of bisphenol A (average number of moles added is preferably 2 to 3) are particularly preferred.
[0017] In addition, from the viewpoint of durability of the toner state, the alcohol component of the polyester resin (A) preferably contains an alkylene oxide adduct of bisphenol A and neopentyl glycol, and more preferably contains at least one alkylene oxide adduct of bisphenol A selected from the group consisting of an EO 2-mol adduct of bisphenol A and a PO 2-mol adduct of bisphenol A, and neopentyl glycol.
[0018] Examples of the tri- or higher hydric polyol (x2) include aliphatic polyhydric alcohols having a valence of 3 to 36 carbon atoms and a valence of tri- or higher, sugars and derivatives thereof, alkylene oxide adducts of aliphatic polyhydric alcohols (average number of moles added is preferably 1 to 30), alkylene oxide adducts of trisphenols (trisphenol PA, etc.) (average number of moles added is preferably 2 to 30), and alkylene oxide adducts of novolak resins (including phenol novolak and cresol novolak, etc., having an average degree of polymerization of preferably 3 to 60) (average number of moles added is preferably 2 to 30).
[0019] Examples of the aliphatic polyhydric alcohol having 3 to 36 carbon atoms and a valence of three or more include alkane polyols and their intramolecular or intermolecular dehydration products, such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, polyglycerin, and dipentaerythritol. Furthermore, examples of sugars and their derivatives include sucrose and methyl glucoside.
[0020] Among these trivalent or higher polyols (x2), from the viewpoint of achieving both low-temperature fixing properties and hot offset resistance, preferred are trivalent or higher aliphatic polyhydric alcohols having 3 to 36 carbon atoms, and alkylene oxide adducts (average number of moles added is preferably 2 to 30) of novolak resins (including phenol novolak and cresol novolak, etc., with an average degree of polymerization preferably being 3 to 60), more preferred are trivalent aliphatic polyhydric alcohols having 3 to 8 carbon atoms, and particularly preferred is trimethylolpropane.
[0021] The diol (x1) in the polyol component (x) of the polyester resin (A) is preferably 80 to 100 mol %. When the diol (x1) and the trihydric or higher polyol (x2) are used in combination, the molar ratio of the diol (x1) to the trihydric or higher polyol (x2) [(x1) / (x2)] is preferably 80 / 20 to 99 / 1, more preferably 85 / 15 to 98 / 2, from the viewpoint of hot offset resistance.
[0022] Furthermore, as the alcohol component of the polyester resin (A), a mono-ol component may be contained, if necessary, in addition to the polyol component (x). Examples of the mono-ol include linear or branched alkyl alcohols having 1 to 30 carbon atoms (methanol, ethanol, isopropanol, 1-decanol, dodecyl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, lignoceryl alcohol, etc.).
[0023] Of these monools, from the viewpoints of image strength and heat-resistant storage stability, linear or branched alkyl alcohols having 8 to 24 carbon atoms are preferred, linear alkyl alcohols having 8 to 24 carbon atoms are more preferred, and dodecyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol and lignoceryl alcohol are even more preferred.
[0024] The carboxylic acid component constituting the polyester resin (A) may contain a polycarboxylic acid component (y) in addition to terephthalic acid. The polycarboxylic acid component (y) includes a dicarboxylic acid (y1) other than terephthalic acid and a trivalent or higher polycarboxylic acid (y2). These may be used alone or in combination of two or more.
[0025] Examples of the dicarboxylic acid (y1) include aromatic dicarboxylic acids having 8 to 36 carbon atoms (phthalic acid, isophthalic acid, naphthalenedicarboxylic acid, etc.), aliphatic dicarboxylic acids having 2 to 50 carbon atoms (oxalic acid, malonic acid, succinic acid, adipic acid, oleaginic acid, sebacic acid, etc.), alicyclic dicarboxylic acids having 6 to 40 carbon atoms [dimer acids (dimerized linoleic acid, etc.)], alkene dicarboxylic acids having 4 to 36 carbon atoms (alkenyl succinic acids such as dodecenyl succinic acid, maleic acid, fumaric acid, citraconic acid, mesaconic acid, etc.), and ester-forming derivatives thereof. Here, the ester-forming derivative means carboxylic acid anhydride, alkyl (methyl, ethyl, butyl, stearyl, etc. having 1 to 24 carbon atoms, preferably those having 1 to 4 carbon atoms) esters, and partial alkyl esters.
[0026] Among these dicarboxylic acids (y1), from the viewpoint of achieving both low-temperature fixability, hot offset resistance, and heat-resistant storage stability, aromatic dicarboxylic acids having 8 to 36 carbon atoms, aliphatic dicarboxylic acids having 2 to 50 carbon atoms, and alkene dicarboxylic acids having 4 to 36 carbon atoms are preferred, phthalic acid, isophthalic acid, adipic acid, succinic acid, maleic acid, and fumaric acid are more preferred, phthalic acid, isophthalic acid, adipic acid, and fumaric acid are even more preferred, and phthalic acid, isophthalic acid, and adipic acid are particularly preferred. In addition, anhydrides and lower alkyl esters of these acids may be used.
[0027] Examples of the trivalent or higher polycarboxylic acid (y2) include trivalent or higher aromatic polycarboxylic acids having 9 to 20 carbon atoms (such as trimellitic acid and pyromellitic acid), aliphatic (including alicyclic) tricarboxylic acids having 6 to 36 carbon atoms (such as hexanetricarboxylic acid and decanetricarboxylic acid), and ester-forming derivatives thereof.
[0028] Among these trivalent or higher polycarboxylic acids (y2), from the viewpoint of achieving both low-temperature fixability and hot offset resistance, aromatic polycarboxylic acids having 9 to 20 carbon atoms are preferred, and trimellitic acid and pyromellitic acid are more preferred. In addition, anhydrides or lower alkyl esters of these acids may also be used.
[0029] The total ratio of terephthalic acid and isophthalic acid in the polycarboxylic acid component of the polyester resin (A) may be 80 to 100 mol %, or may be 100 mol %. In other words, the polyester resin (A) may not contain any carboxylic acid component other than terephthalic acid and isophthalic acid as the polycarboxylic acid component.
[0030] Furthermore, as the carboxylic acid component of the polyester resin (A), a monocarboxylic acid component can be contained as necessary. Examples of the monocarboxylic acid include aromatic monocarboxylic acids having 7 to 37 carbon atoms (benzoic acid, toluic acid, 4-ethylbenzoic acid, 4-propylbenzoic acid, etc.), and aliphatic (including alicyclic) monocarboxylic acids having 2 to 50 carbon atoms (acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, behenic acid, etc.).
[0031] Among these monocarboxylic acids, aromatic monocarboxylic acids having 7 to 37 carbon atoms are preferred, and benzoic acid is more preferred, from the viewpoints of image strength and heat-resistant storage stability.
[0032] The acid value of the polyester resin (A) is preferably from 0 to 30 mgKOH / g, and more preferably from 0.1 to 10 mgKOH / g, from the viewpoints of low-temperature fixability, charge retention rate, and durability of print quality. The acid value can be measured by the method specified in JIS K0070.
[0033] The glass transition temperature of the polyester resin (A) is preferably from 50 to 70°C, and more preferably from 55 to 65°C, from the viewpoints of heat-resistant storage stability and low-temperature fixability. The glass transition temperature (Tg) of the polyester resin (A) can be determined by the method (DSC method) specified in ASTM D3418-82. For example, DSC Q20 manufactured by TA Instruments Co., Ltd. can be used to measure the glass transition temperature (Tg). The glass transition temperature (Tg) can be measured under the following conditions. <Measurement conditions> (1) Heat from 30°C to 150°C at 20°C / min (2) Hold at 150°C for 10 minutes (3) Cool to -35°C at 20°C / min (4) Keep at -35℃ for 10 minutes (5) Heat up to 150°C at 20°C / min. (6) The differential scanning calorimetry curve measured in the process of (5) is analyzed, and the position of the inflection point is determined as the glass transition temperature.
[0034] The weight average molecular weight of the polyester resin (A) is preferably from 3,000 to 10,000, and more preferably from 5,000 to 9,000, from the viewpoints of low-temperature fixability and durability of print quality.
[0035] In the present invention, the weight average molecular weight and the peak top molecular weight can be measured by gel permeation chromatography (GPC) under the following conditions. Equipment (example): Tosoh Corporation HLC-8120 Column (example): 2 TSK GEL GMH6 [Tosoh Corporation] Measurement temperature: 40℃ Sample solution: 0.25% by weight in THF Solution injection volume: 100μL Detector: Refractive index detector Reference material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) manufactured by Tosoh Corporation (molecular weight: 500, 1,050, 2,800, 5,970, 9,100, 18,100, 37,900, 96,400, 190,000, 355,000, 1,090,000, 2,890,000) For the measurement of molecular weight, a sample is dissolved in tetrahydrofuran (THF) to a concentration of 0.25% by weight, and the insoluble matter is filtered off using a PTFE filter with an aperture of 220 nm to obtain a sample solution. For the polyester resin (B) and the image-forming material described below, the weight average molecular weight and the peak top molecular weight can be determined in the same manner as above.
[0036] The polyester resin (A) can be obtained by mixing ethylene glycol and terephthalic acid and carrying out a polycondensation reaction in the presence of a polymerization catalyst. The terephthalic acid component contained in the polyester resin (A) may be a terephthalic acid component derived from PET (polyethylene terephthalate). In this case, the polyester resin (A) can be obtained by mixing ethylene glycol and PET and carrying out a polycondensation reaction in the presence of a polymerization catalyst.
[0037] Specifically, the polyester resin (A) can be produced, for example, as follows: For example, ethylene glycol and terephthalic acid are subjected to a polycondensation reaction in an inert gas (such as nitrogen gas) atmosphere at a reaction temperature of preferably 150 to 280°C, more preferably 160 to 250°C, and even more preferably 170 to 235°C. From the viewpoint of ensuring the polycondensation reaction, the reaction time is preferably 30 minutes or more, more preferably 2 to 40 hours. It is also effective to reduce pressure in order to improve the reaction rate at the end of the reaction.
[0038] During this reaction, a polyol component other than ethylene glycol, a (poly)carboxylic acid component other than terephthalic acid may be added, and if necessary, a silicone resin (C) may be included.
[0039] In this case, an esterification catalyst can be used as necessary. Examples of the esterification catalyst include tin-containing catalysts (e.g., dibutyltin oxide, etc.), antimony trioxide, titanium-containing catalysts [e.g., titanium alkoxides (tetrabutoxytitanate, etc.), potassium oxalate titanate, titanium terephthalate, titanium alkoxide terephthalate, catalysts described in JP-A-2006-243715 {titanium diisopropoxybis(triethanolaminate), titanium dihydroxybis(triethanolaminate), titanium monohydroxytris(triethanolaminate), titanyl bis(triethanolaminate) and their intramolecular polycondensates, etc.} and catalysts described in JP-A-2007-11307 (titanium tributoxyterephthalate, titanium triisopropoxyterephthalate, titanium diisopropoxyditerephthalate, etc.)], zirconium-containing catalysts (e.g., zirconyl acetate, etc.) and zinc acetate, etc. Among these, titanium-containing catalysts are preferred.
[0040] In order to stably proceed with the polymerization of the polyester, a stabilizer may be added, such as hydroquinone, methylhydroquinone, and a hindered phenol compound.
[0041] Next, the image forming material for a toner binder of the present invention may contain a polyester resin (B) other than the polyester resin (A). The polyester resin (B) is a polyester resin obtained by polycondensing an alcohol component and a carboxylic acid component, but the alcohol component does not contain ethylene glycol, or the carboxylic acid component does not contain terephthalic acid.
[0042] The polyester resin (B) is preferably a non-linear polyester resin. A "non-linear" polyester resin is a polyester resin having branches (crosslinking points) in the main chain.
[0043] The alcohol component in the polyester resin (B) may be the same as the polyol component (x) that can be contained in the polyester resin (A). In addition, if the carboxylic acid component does not contain terephthalic acid, the alcohol component may contain ethylene glycol.
[0044] The polyol component (x) in the polyester resin (B) is preferably an alkylene glycol having 3 to 36 carbon atoms, an alkylene oxide adduct of bisphenol A, an alkylene oxide adduct of a novolak resin, or the like, and more preferably propylene glycol, a 2-mol PO adduct of bisphenol A, a 3-mol PO adduct of bisphenol A, an EO 5.6-mol adduct of phenol novolak, or the like.
[0045] The carboxylic acid component in the polyester resin (B) may be the same as the polycarboxylic acid component (y) and monocarboxylic acid component that can be contained in the polyester resin (A). In addition, the carboxylic acid component may contain terephthalic acid as long as the alcohol component does not contain ethylene glycol.
[0046] The polycarboxylic acid component (y) in the polyester resin (B) is preferably an aromatic dicarboxylic acid having 8 to 36 carbon atoms, or a trivalent or higher aromatic polycarboxylic acid having 9 to 20 carbon atoms, and more preferably adipic acid or trimellitic anhydride.
[0047] The acid value of the polyester resin (B) is preferably from 5 to 60 mgKOH / g, and more preferably from 10 to 45 mgKOH / g, from the viewpoints of low-temperature fixability, charge retention rate, and durability of print quality. The glass transition temperature of the polyester resin (B) is preferably from 50 to 70°C, and more preferably from 55 to 65°C, from the viewpoints of heat-resistant storage stability and low-temperature fixability. The peak top molecular weight of the polyester resin (B) is preferably from 2,000 to 300,000, and more preferably from 3,000 to 150,000, from the viewpoints of low-temperature fixability and durability of print quality. The acid value, glass transition temperature and peak top molecular weight of the polyester resin (B) can be measured in the same manner as for the polyester resin (A).
[0048] The image-forming material for a toner binder of the present invention contains a silicone resin (C).
[0049] The silicone resin (C) is a curable silicone resin, and preferably a silicone resin containing a repeating unit of dimethylsiloxane. The curable silicone resin is a resin obtained by curing a silicone resin having an organopolysiloxane structure as the main chain. Examples of the curable silicone resin include an "addition reaction curable type" in which an organohydrogenpolysiloxane and an organopolysiloxane containing an alkenyl group are heat-cured under a platinum catalyst, a "condensation reaction curable type" in which an organohydrogenpolysiloxane and an organopolysiloxane containing a hydroxyl group at the end are heat-cured using an organotin catalyst, a "UV curable type" in which a photopolymerization initiator is blended with an organopolysiloxane containing an acryloyl group or a methacryloyl group, or an organopolysiloxane containing an alkenyl group and an organopolysiloxane containing a mercapto group, and the resin is cured by irradiating the resin with UV light, and a "cationic polymerization curable type" in which an epoxy group is photo-ring-opened with an onium salt initiator and cured. Either type may be used, but from the viewpoint of productivity, addition reaction type or UV curing type is preferred.
[0050] Specific examples of addition reaction curing silicone resins include those containing polydimethylsiloxane containing vinyl groups at the terminals and hydrogensiloxane, and include KS-847, KS-847T, KS-841, KS-774, KS-3703T, and X-62-2825 manufactured by Shin-Etsu Chemical Co., Ltd., and SD7333, SRX357, SRX345, LTC310, LTC303E, LTC300B, LTC350G, LTC750A, LTC851, LTC759, LTC755, LTC761, and LTC856 manufactured by Dow-Toray Industries, Inc. (note that "LTC" is a registered trademark).
[0051] Specific examples of the condensation reaction curing silicone resin and catalyst are preferably those containing polydimethylsiloxane and hydrogensiloxane containing hydroxyl groups at the terminals and an organotin catalyst, such as SRX290 and SY LOFF23 manufactured by Dow Toray Industries, Inc.
[0052] Specific examples of the UV-curable silicone resin and catalyst include those containing an organopolysiloxane containing an acryloyl group or a methacryloyl group and a photopolymerization initiator, and those containing a polydimethylsiloxane containing an alkenyl group, a polydimethylsiloxane containing a mercapto group, and a photopolymerization initiator, and examples of such UV-curable silicone resin and catalyst include FM-0711, FM-0721, FM-0725, FM-7711, FM-7721, and FM-7725 manufactured by JNC Corporation, and BY24-510H and BY24-544 manufactured by Dow-Toray Industries, Inc.
[0053] Specific examples of the cationic polymerization curing silicone resin and catalyst are preferably those containing a siloxane containing an epoxy group and an onium salt initiator, such as TPR6501, UV9300, and XS56-A2775 manufactured by Momentive Performance Materials Japan, LLC.
[0054] When synthesizing silicone resin (C), the amount of organohydrogenpolysiloxane used is preferably 0.2-40 parts by weight relative to 100 parts by weight of the organopolysiloxane component. In order to promote the addition reaction of these silicone resins by heat, a platinum catalyst or the like is made to coexist, and in order to promote the addition reaction by ultraviolet light, a photopolymerization initiator or the like is made to coexist, so that the curing reaction can be achieved relatively quickly and the desired silicone resin can be formed.In addition, this silicone resin can also be further blended with a known reaction inhibitor, an inorganic filler such as silica, or a pigment as necessary within the scope of the present invention.
[0055] In simultaneous thermogravimetry and differential thermal analysis, the silicone resin (C) preferably exhibits a weight loss of 40% by weight or less, and more preferably 30% by weight or less, in the range of 250°C to 500°C when heated from 100°C to 500°C at a heating rate of 10°C / min, from the viewpoint of hot offset resistance. The weight loss of the silicone resin (C) can be controlled to 40% by weight or less by adjusting the molecular weight of the silicone resin.
[0056] The weight loss of the silicone resin (C) can be calculated by the following formula. Weight loss of silicone resin (C) (weight%) = Weight loss at 500°C (weight%) - Weight loss at 250°C (weight%) Weight loss at 500℃ (wt%): (initial weight - weight at 500℃) / initial weight x 100 Weight loss at 250℃ (wt%): (initial weight - weight at 250℃) / initial weight x 100
[0057] The weight loss of the silicone resin (C) can be measured using NEXTA STA200 or the like manufactured by Yamato Scientific Co., Ltd. The weight loss can be measured under the following conditions. <Measurement conditions> (1) Heat from 30°C to 100°C at 10°C / min (2) Hold at 100°C for 60 minutes (3) Heat from 100°C to 500°C at 10°C / min
[0058] The image forming material for toner binder of the present invention may contain, in addition to the polyester resin (A), the polyester resin (B) and the silicone resin (C), a vinyl resin, an epoxy resin, a polyurethane resin, a polycarbonate resin, a crystalline polyester resin, a crystalline vinyl resin, or the like.
[0059] When the image-forming material for toner binder of the present invention contains components other than the polyester resin (A) and the silicone resin (C), the weight proportion of the polyester resin (A) is preferably 10 to 90% by weight, and more preferably 10 to 80% by weight, based on the weight of the image-forming material (100% by weight). When the weight ratio of the polyester resin (A) is 10% by weight or more, the fixing width of the toner can be made wider, and when the weight ratio of the polyester resin (A) is 90% by weight or less, the chargeability (charge retention rate) of the toner becomes better.
[0060] When the image forming material for toner binder of the present invention contains components other than the polyester resin (A) and the silicone resin (C), the weight ratio of the silicone resin (C) is 0.1 to 1 weight%, preferably 0.1 to 0.7 weight%, and more preferably 0.1 to 0.5 weight%, based on the weight of the image forming material (100 weight%). If the weight ratio of the silicone resin (C) is less than 0.1 weight%, improvement in hot offset resistance cannot be obtained, and if it exceeds 1 weight%, low temperature fixability is deteriorated.
[0061] When the image forming material for toner binder of the present invention further contains a polyester resin (B), the weight ratio of the polyester resin (A) to the total of the polyester resins (A) and (B) (100% by weight) is preferably 10 to 90% by weight, and more preferably 10 to 80% by weight. When the weight ratio of the polyester resin (A) is 10% by weight or more, the fixing width of the toner can be made wider, and when the weight ratio of the polyester resin (A) is 90% by weight or less, the chargeability (charge retention rate) of the toner becomes better.
[0062] The image forming material for toner binder of the present invention may contain one or more types of polyester resins (A), one or more types of polyester resins (B), and one or more types of silicone resins (C). When multiple types of polyester resins (A), polyester resins (B), or silicone resins (C) are contained, the content of each is the total amount of each of the polyester resins (A), polyester resins (B), and silicone resins (C).
[0063] The image forming material for a toner binder of the present invention can be preferably used for toner applications. When used in toner applications, the toner may contain, if necessary, one or more known additives selected from colorants, release agents, charge control agents, fluidizing agents, and the like.
[0064] As the colorant, all of the dyes and pigments used as toner colorants can be used. For example, carbon black, iron black, Sudan Black SM, Fast Yellow G, Benzidine Yellow, Pigment Yellow, India Fast Orange, Irgasin Red, Paranitroaniline Red, Toluidine Red, Carmine FB, Pigment Orange R, Lake Red 2G, Rhodamine FB, Rhodamine B Lake, Methyl Violet B Lake, Phthalocyanine Blue, Pigment Blue, Brilliant Green, Phthalocyanine Green, Oil Yellow GG, Kayaset YG, Orazol Brown B, and Oil Pink OP can be mentioned. The colorant may be any one of these alone or a mixture of two or more. In addition, if necessary, magnetic powder (powder of ferromagnetic metals such as iron, cobalt, and nickel, or compounds such as magnetite, hematite, and ferrite) can be contained to function as a colorant. The content of the colorant is preferably 1 to 40 parts by weight, more preferably 3 to 10 parts by weight, based on 100 parts by weight of the image forming material for the toner binder of the present invention. When a magnetic powder is used, the content is preferably 20 to 150 parts by weight, more preferably 40 to 120 parts by weight, based on 100 parts by weight of the image forming material.
[0065] Examples of the release agent include aliphatic hydrocarbon waxes such as low molecular weight polypropylene, low molecular weight polyethylene, low molecular weight polypropylene-polyethylene copolymers, polyolefin wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; carnauba wax, montan wax, sazol wax, and deacidified waxes thereof; ester waxes such as fatty acid ester wax; fatty acid amides; fatty acids; higher alcohols; fatty acid metal salts; and mixtures thereof.
[0066] Examples of polyolefin waxes include (co)polymers of olefins (e.g., ethylene, propylene, 1-butene, isobutylene, 1-hexene, 1-dodecene, 1-octadecene, and mixtures thereof) [including those obtained by (co)polymerization and thermally degradable polyolefins], oxides of olefin (co)polymers with oxygen and / or ozone, maleic acid modified products of olefin (co)polymers [e.g., products modified with maleic acid and its derivatives (maleic anhydride, monomethyl maleate, monobutyl maleate, dimethyl maleate, etc.)], copolymers of olefins and unsaturated carboxylic acids [(meth)acrylic acid, itaconic acid, maleic anhydride, etc.] and / or unsaturated carboxylic acid alkyl esters [(meth)acrylic acid alkyl (C1-18 alkyl) esters and maleic acid alkyl (C1-18 alkyl) esters, etc.], and Sasol wax.
[0067] The higher alcohol is an aliphatic alcohol having 30 to 50 carbon atoms, for example, triacontanol. The fatty acid is an aliphatic alcohol having 30 to 50 carbon atoms, for example, triacontanol.
[0068] Examples of the charge control agent include nigrosine dyes, triphenylmethane dyes containing a tertiary amine as a side chain, quaternary ammonium salts, polyamine resins, imidazole derivatives, polymers containing a quaternary ammonium base, metal-containing azo dyes, copper phthalocyanine dyes, metal salicylic acid salts, boron complexes of benzilic acid, sulfonic acid group-containing polymers, fluorine-containing polymers, and halogen-substituted aromatic ring-containing polymers. A specific example of the charge control agent is T-77 (azo-based iron complex manufactured by Hodogaya Chemical Co., Ltd.).
[0069] Examples of the fluidizing agent include colloidal silica, alumina powder, and titanium oxide powder.
[0070] Other additives include melamine compounds.
[0071] The content of the colorant is preferably 0.05 to 60% by weight, more preferably 0.1 to 55% by weight, and even more preferably 0.5 to 50% by weight, based on the weight of the toner. The content of the releasing agent is preferably 0 to 30% by weight, more preferably 0.5 to 20% by weight, and further preferably 1 to 10% by weight, based on the weight of the toner. The content of the charge control agent is preferably 0 to 20% by weight, more preferably 0.1 to 10% by weight, and further preferably 0.5 to 7.5% by weight, based on the weight of the toner. The content of the fluidizing agent is preferably 0 to 10% by weight, more preferably 0 to 5% by weight, and further preferably 0.1 to 4% by weight, based on the weight of the toner. The total content of the additives is preferably from 3 to 70% by weight, more preferably from 4 to 58% by weight, and even more preferably from 5 to 50% by weight, based on the weight of the toner. By setting the composition ratio of the toner within the above range, it is possible to easily obtain a toner having good low-temperature fixing properties, hot offset resistance, chargeability (charge retention rate), durability of print quality, and toner durability.
[0072] In the image-forming material for toner binder of the present invention, the polyester resin (A) and the silicone resin (C) may be mixed after the synthesis of the polyester resin (A), or the silicone resin (C) may be added during the synthesis of the polyester resin (A). Also, the silicone resin (C) may become a silicone-containing polyester resin.
[0073] When the image forming material for toner binder of the present invention is used for toner applications, it becomes a toner. The toner may be obtained by any of the known methods such as a kneading and pulverizing method, an emulsion phase inversion method, and a polymerization method. For example, when a toner is obtained by a kneading and pulverizing method, the components constituting the toner except for the fluidizing agent are dry-blended, melt-kneaded, then coarsely pulverized, and finally, the toner is pulverized using a jet mill pulverizer or the like, and further classified to obtain fine particles having a volume average particle size (D50) of preferably 5 to 20 μm, and then the fluidizing agent is mixed therein to produce the toner. The volume average particle size (D50) is measured using a Coulter counter {for example, trade name: Multisizer III [manufactured by Beckman Coulter, Inc.]}.
[0074] In addition, when the toner is obtained by the emulsion phase inversion method, the components constituting the toner except for the fluidizing agent are dissolved or dispersed in an organic solvent, and then emulsified by adding water or the like, followed by separation and classification to produce the toner. The volume average particle size of the toner is preferably 3 to 15 μm.
[0075] The toner is mixed with carrier particles such as iron powder, glass beads, nickel powder, ferrite, magnetite, and ferrite coated with resin (acrylic resin, non-curing silicone resin, etc.) as necessary, and used as a developer for an electric latent image. When carrier particles are used, the weight ratio of the toner to the carrier particles is preferably 1 / 99 to 99 / 1. Also, the toner can be rubbed against a member such as a charging blade instead of the carrier particles to form an electric latent image. The toner does not necessarily need to contain carrier particles.
[0076] The toner is fixed to a support (paper, polyester film, etc.) to form a recording material by a copier, printer, etc. As a method for fixing to a support, a known heat roll fixing method, flash fixing method, etc. can be used.
[0077] The toner and the image forming material for the toner binder of the present invention are used for developing electrostatic images or magnetic latent images in electrophotography, electrostatic recording, electrostatic printing, etc. More specifically, they are used for developing electrostatic images or magnetic latent images that are particularly suitable for full color. EXAMPLES
[0078] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited to these.
[0079] <Production Example 1> Synthesis of polyester resin (A1) In a reaction vessel, 330 parts by weight of ethylene glycol, 480 parts by weight of bisphenol A·PO 2-mol adduct, 558 parts by weight of PET flakes (commercially available PET bottles cut into 1 cm squares), and 1 part by weight of tetrabutoxytitanate as a condensation catalyst were placed and reacted for 5 hours under a nitrogen stream at 220°C while distilling off the water produced, then reacted under reduced pressure of 0.5 to 2.5 kPa, and cooled to 175°C when the acid value became 2 mgKOH / g or less. Next, 15 parts by weight of trimellitic anhydride was placed and esterified at normal pressure for 1 hour at 175°C, after which the mixture was removed to obtain polyester resin (A1). The polyester resin (A1) had a Tg of 65° C. and a weight average molecular weight of 6,300.
[0080] <Production Examples 2 to 4, 8, 9, and 11> Synthesis of polyester resins (A2) to (A4), (A8), (A9), and (A11) Polyester resins (A2) to (A4), (A8), (A9), and (A11) were obtained in the same manner as in Example 1, except that the compositions shown in Table 1 were used.
[0081] <Production Example 5> Synthesis of polyester resin (A5) A reaction tank was charged with 294 parts by weight of ethylene glycol, 6 parts by weight of neopentyl glycol, 762 parts by weight of PET flakes (commercially available PET bottles cut into 1 cm squares), 283 parts by weight of isophthalic acid, and 1 part by weight of tetrabutoxytitanate as a condensation catalyst, and the mixture was reacted for 5 hours at 220°C under a nitrogen stream while distilling off the water produced, and then reacted under a reduced pressure of 0.5 to 2.5 kPa. When the acid value reached 1 mgKOH / g, the mixture was removed to obtain a polyester resin (A5). The polyester resin (A5) had a Tg of 60° C. and a weight average molecular weight of 7,600.
[0082] <Production Examples 6, 7, and 10> Synthesis of polyester resins (A6), (A7), and (A10) Polyester resins (A6), (A7), and (A10) were obtained in the same manner as in Example 5, except that the compositions shown in Table 1 were used.
[0083] Comparative Production Example 1: Synthesis of polyester resin (RA1) A reaction tank was charged with 500 parts by weight of ethylene glycol, 830 parts by weight of isophthalic acid, and 1 part by weight of tetrabutoxytitanate as a condensation catalyst, and reacted for 5 hours at 220°C under a nitrogen stream while distilling off the water produced, and then reacted under a reduced pressure of 0.5 to 2.5 kPa. When the acid value reached 0.5 mgKOH / g, the mixture was removed to obtain a polyester resin (RA1). The polyester resin (RA1) had a Tg of 60° C. and a weight average molecular weight of 5,800.
[0084] Comparative Production Example 2: Synthesis of polyester resin (RA2) A reaction vessel was charged with 774 parts by weight of bisphenol A·PO 2-mol adduct, 288 parts by weight of terephthalic acid, and 1 part by weight of tetrabutoxytitanate as a condensation catalyst, and the mixture was reacted at 220°C under a nitrogen stream for 5 hours while distilling off the water that was produced. The mixture was then reacted under a reduced pressure of 0.5 to 2.5 kPa, and the mixture was removed when the acid value reached 0.2 mg KOH / g to obtain polyester resin (RA2). The polyester resin (RA2) had a Tg of 70° C. and a weight average molecular weight of 6,000.
[0085] Table 1 shows the physical properties of the polyester resins (A1) to (A11) and (RA1) to (RA2).
[0086] [Table 1]
[0087] <Production Example 12> Synthesis of polyester resin (B1) In a reaction vessel, 140 parts by weight of bisphenol A·PO 2-mol adduct, 600 parts by weight of bisphenol A·PO 3-mol adduct, 32 parts by weight of phenol novolac EO 5.6-mol adduct, 176 parts by weight of terephthalic acid, 17 parts by weight of trimellitic anhydride (5.2 mol%), and 1 part by weight of tetrabutoxy titanate as a condensation catalyst were placed, and reacted for 4 hours under a nitrogen stream at 220°C while distilling off the water produced, and then reacted for 2 hours under a reduced pressure of 0.5 to 2.5 kPa. Then, 90 parts by weight of trimellitic anhydride was added at 210°C, and reacted for 1 hour under normal pressure, and then reacted for 10 hours under a reduced pressure of 0.5 to 5 kPa, and taken out. The obtained resin was cooled to room temperature, crushed, and granulated to obtain polyester resin (B1). The polyester resin (B1) had a Tg of 59° C. and a peak top molecular weight of 6200. The physical properties of the polyester resin (B1) are shown in Table 2.
[0088] <Production Example 13> Synthesis of polyester resin (B2) In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 715 parts by weight of propylene glycol, 740 parts by weight of terephthalic acid, 35 parts by weight of adipic acid, and 1 part by weight of tetrabutoxy titanate as a polymerization catalyst were placed and reacted for 12 hours under nitrogen flow at 180°C while distilling off the water generated. Then, the temperature was gradually raised to 230°C, and the reaction was carried out for 4 hours under nitrogen flow while removing the water generated, and the reaction was further carried out under reduced pressure of 0.7 to 2.7 kPa, and the reaction was cooled when the softening point reached 88°C. The amount of propylene glycol recovered was 325 parts by weight. Then, the reaction was cooled to 180°C, and 50 parts by weight of trimellitic anhydride was added, and the reaction was carried out for 2 hours under sealed conditions, followed by reaction at 220°C under reduced pressure of 2.7 to 5.3 kPa and removal at a predetermined softening point. The resin obtained was cooled to room temperature, pulverized and granulated to obtain polyester resin (B2). The polyester resin (B2) had a Tg of 60° C. and a peak top molecular weight of 4500. The physical properties of the polyester resin (B2) are shown in Table 2.
[0089] [Table 2]
[0090] <Production Example 14> Synthesis of Silicone Resin (C1) 100 parts by weight of thermosetting silicone resin [KS-847T: manufactured by Shin-Etsu Chemical Co., Ltd.] was added with 3 parts by weight of platinum catalyst [CAT-PL-50T: manufactured by Shin-Etsu Chemical Co., Ltd.] and stirred. The solvent was removed by an evaporator to prepare a curable silicone resin composition. This curable silicone resin composition was heated at 170°C for 2 hours, and the obtained cured product was pulverized to obtain silicone resin (C1), which is a cured product of the curable silicone resin. Simultaneous thermogravimetric and differential thermal analysis of silicone resin (C1) showed that when it was heated from 100°C to 500°C at a heating rate of 10°C / min, the weight loss in the range of 250°C to 500°C was 28% by weight.
[0091] <Examples 1 to 12 and Comparative Examples 1, 2, and 4> Polyester resin (A), polyester resin (B) and silicone resin (C1) were mixed according to the mixing ratios (parts by weight) in Table 3 to obtain toner binders (TB1) to (TB12), (RTB1), (RTB2) and (RTB4), respectively.
[0092] Next, the toner binders (TB1) to (TB12), (RTB1), (RTB2) and (RTB4) were premixed with the colorant, release agent and charge control agent using a Henschel mixer [FM10B, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.], and then kneaded with a twin-screw kneader [PCM-30, manufactured by Ikegai Co., Ltd.]. Next, the mixture was finely pulverized using a supersonic jet pulverizer Labojet [manufactured by Nippon Pneumatic Industrial Co., Ltd.], and then classified with an air classifier [MDS-I, manufactured by Nippon Pneumatic Industrial Co., Ltd.] to obtain toner particles with a particle size D50 of 7 μm. Furthermore, 100 parts by weight of the toner particles were mixed with 0.5 parts by weight of colloidal silica [Aerosil R972: manufactured by Nippon Aerosil Co., Ltd.] in a sample mill to obtain toners (TC1) to (TC12), (RC1), (RC2) and (RC4), which are image forming materials for the toner binder of the present invention.
[0093] <Comparative Example 3> Similarly to Example 1, the ingredients were mixed according to the mixing ratios shown in Table 3, and a toner binder (RTB3) and a toner (RTC3) were obtained in the same manner as in Example 1, except that the silicone resin (C1) was not used.
[0094] The colorants, release agents, and charge control agents in Table 3 are as follows: Colorant: Carbon black MA-100 [Mitsubishi Chemical Co., Ltd.] Release agent: Carnauba wax [Toyo Adle Co., Ltd.] Charge control agent: T-77 [Hodogaya Chemical Co., Ltd.]
[0095] [Evaluation method] [1] Low-temperature fixability Using the above toner, an unfixed image developed using a commercially available copier [AR5030; manufactured by Sharp Corporation] was evaluated using the fixing device of the commercially available copier [AR5030; manufactured by Sharp Corporation]. The fixing roll temperature at which the residual rate of the image density measured using a Macbeth reflection densitometer RD-191 [manufactured by Macbeth Corporation] after rubbing the fixed image with a pad was 75% or more was defined as the minimum fixing temperature (MFT) (°C). The lower the MFT, the better the low-temperature fixing property. The MFT is shown as low temperature fixability (° C.) in Table 3. A low temperature fixability of 135° C. or less is considered to be good.
[0096] [2] Release properties (hot offset resistance) The occurrence of hot offset in the fixed image was visually evaluated in the same manner as in the above-mentioned low-temperature fixing property evaluation method. The fixing roll temperature at which hot offset occurred was defined as the hot offset occurrence temperature (HOT) (°C). The higher the HOT, the better the hot offset resistance. In Table 3, HOT is shown as hot offset resistance (° C.). Hot offset resistance of 220° C. or higher is considered good.
[0097] [3] Fixation width The value obtained by subtracting MFT from HOT is the fixing width (℃) and is shown in Table 3. The larger the fixing width, the better the balance between low temperature fixing property and hot offset resistance. A fixing width of 100℃ or more is good.
[0098] [4] Durability Using a commercially available copier [MX-M754FN, manufactured by Sharp Corporation], the toner was removed, the carrier and toner were separated, and the inside of the cartridge was cleaned with an air blower. The toner and carrier were then mixed together and conditioned for 14 days at 40°C and 50% relative humidity. This allows durability to be evaluated under more severe conditions. Using this as a two-component developer, continuous copies were made at a printing speed of 75 sheets / min, and the print status of 2,000 sheets, 6,000 sheets, and 10,000 sheets was confirmed, and part of the toner was extracted to measure the particle size, and durability was evaluated according to the following criteria. The volume average particle size (D50) was measured using a Coulter counter {product name: Multisizer III [manufactured by Beckman Coulter, Inc.]}. The results are shown in Table 3. [Judgment criteria] <Print quality> ⊚: No change in image quality or fogging even after 10,000 copies. ◯: Fog occurs after 10,000 copies. △: Fog occurs after 6,000 copies. ×: Fog occurs after 2,000 copies. <Toner status> ◎: The change in particle size D50 is less than 3%, and no fine powder of 2 μm or less is observed. ○: The change in particle size D50 is 3 to 5%, and no fine powder of 2 μm or less is observed. ×: The change in particle size D50 exceeds 5%, or fine powder of 2 μm or less is generated. Under these evaluation conditions, it is preferable that both the print quality and the toner condition are in the range of ◯ or ⊚.
[0099] [Table 3]
[0100] The toners of the examples containing the polyester resin (A) and the silicone resin (C) were excellent in releasability, durability, and sufficiently wide fixing width, whereas the toners of the comparative examples were inferior in performance in at least one evaluation item. [Industrial Applicability]
[0101] The image forming material for toner binder in the present invention is excellent in durability and releasability and has a wide fixing width, and therefore can be suitably used as a toner for developing electrostatic images used in electrophotography, electrostatic recording, electrostatic printing, etc. Furthermore, it can be suitably used as a surface modifier for inkjet recording media.
Claims
1. An image-forming material for toner binder, comprising a polyester resin (A) obtained by polycondensing an alcohol component and a carboxylic acid component, and a silicone resin (C), The polyester resin (A) is characterized in that the alcohol component contains ethylene glycol, the carboxylic acid component contains terephthalic acid, and the silicone resin (C) is a cured product of a curable silicone resin, The image-forming material for toner binder, wherein the weight ratio of the silicone resin (C) in the image-forming material is 0.1 to 1% by weight.
2. 2. The image forming material for a toner binder according to claim 1, wherein the silicone resin (C) is a silicone resin containing a repeating unit of dimethylsiloxane.
3. 3. The image forming material for toner binder according to claim 1, wherein a weight loss of the silicone resin (C) is 40% by weight or less in a range of 250° C. to 500° C. when the temperature is increased from 100° C. to 500° C. at a heating rate of 10° C. / min in simultaneous thermogravimetry and differential thermal analysis.
4. 3. The image-forming material for toner binder according to claim 1, wherein the weight ratio of said polyester resin (A) in said image-forming material is from 10 to 90% by weight.
5. 3. The image forming material for a toner binder according to claim 1, wherein the alcohol component of the polyester resin (A) contains an alkylene oxide adduct of bisphenol A.
Citation Information
Patent Citations
Internally added releasing agent for toner and toner using same
JP1995244398A